Modern Approaches to Quality Evaluation of Enzyme-Linked Immunoassay Diagnostic Kits - Shchetinin, Valeria (Innovative Biosystems and Bioengineering, 2020)
Background. Enzyme-linked immunoassay (ELISA) diagnostic kits are a medical device designed to solve an important task as patient's life and health depend on the correctness of laboratory test result. Therefore, at present, special attention is given to the quality of in vitro diagnostic medical devices, which in turn is related to standardization and technical regulation. Objective. The goal of the work was analysis of up-to-date methodological approaches to quality assessment of ELISA diagnostic kits. Methods. The results of the development, standardization, and testing of ELISA kits, as well as the recommendations of international institutions and certification bodies, were studied and analyzed. Results. Properties of biological components of diagnostic kits (immunoenzymatic conjugates and immunosorbents) were analyzed; their impact on diagnostic quality level of ELISA kits was determined. The current methodology for assessing the quality conjugates and immunoassay diagnostic kits, in general, was analyzed. The important role of standardized sera panels (qualification, verification, seroconversion, expert, and sensitivity panels) in the assessment procedure for the diagnostic ELISA kits has been demonstrated. The methods of obtaining control materials used to assess the quality of diagnostic kits were analyzed. Special attention was paid to methods to ensure the stability of control materials. Conclusions. In the case of the most socially important infections (HIV, hepatitis B and C), strict values of specificity and sensitivity have been established by regulatory authorities and/or international institutions. In the case of other diseases, rationing of diagnostic indicators has to be performed (justified) by research and development group and/or by the manufacturer.